PROSPECTS OF PROPERTY IN CHINATOWN SURABAYA CASE STUDY: KEMBANG JEPUN STREET SURABAYA - Ni Wayan Anantasia Saraswati; Purwanita Setijanti; Murni Rachmawati (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Kembang Jepun area was once the biggest trade center in its time. However, its ambience is quiet and crime-prone today, especially at night. This is caused by the decrease of service value of the areal facilities and infrastructures, so that it in turn decreases the areal economic productivity. This condition requires a research about the most suitable property which can be developed according to the desire of the society in the corridor of Kembang Jepun Street and can revive the ‘dead’ areal spirit.This research applies interview method along with market analysis. The type of analysis is Descriptive Statistics, namely by the media of graphics, diagrams and tables.From the interview result, retails are found to be prospective property for the society in the Corridor of Kembang Jepun Street. The next analysis conducted as the comparator to the survey result is Market Analysis on five property buildings, namely retails, hotels, museums, restaurants and residences. Having the market analysis done, a conclusion is found that Hotels property is more prospective than retails, museums, restaurants and residences property with the consideration of dominant supply of hotels in Central Surabaya, East Surabaya and West Surabaya, as well as that hotels have lesser competitors with quite high demands.